EFEKTIVITAS DAN KONTRIBUSI PAJAK MINERAL BUKAN LOGAM DAN BATUAN TERHADAP PAJAK DAERAH DI KABUPATEN TULUNGAGAGUNG - Wulandari, Dewi; Srihastuti , Eni; Agustin , Beby Hilda (Jurnal Ilmiah Mahasiswa Nias Selatan, 2023)
Regionalgtaxesgaregtaxesgcollectedgbyglocalggovernmentsgtogfinancegregional gdevelopment. gThis study aims to find out how the effectiveness and contribution of non-metallic mineral and rock taxes to local taxes during 2018-2021. This research is a quantitative descriptive research that is, based on the explanation of the numbers. The data in this study are in the form of targets and realization of non-metal mineral and rock tax revenues, as well as data on the realization of Regional Taxes for Tulungagung district for four years. Data collection techniques using documentation and interviews. The results of the study show that the effectiveness of the tax on non-metallic minerals and rocks in 2018-2021 is in the very effective category. The highest level of effectiveness occurred in 2020, which was 113.41% and the lowest level occurred in 2019, which was 101.23%. For the level of tax contribution of non-metallic minerals and rocks to regional taxes, it shows that for a period of four years every year it has decreased and is included in the very less category. The highest contribution rate occurred in 2018, which was 0.36% and the lowest contribution rate occurred in 2021, which was 0.20%.